Electronic Transport Through Double Quantum Dot Coupled to Majorana Bound States and Ferromagnetic Leads - Tang, Li-Wen; Mao, Wei-Guo (Frontiers in Physics, 2021)
We have studied theoretically the properties of electrical current and tunnel magnetoresistance (TMR) through serially connected double-quantum-dot (DQD) sandwiched between two ferromagnetic leads by using the nonequilibrium Green’s function technique. We consider that each of the DQD couples to one mode of the Majorana bound states (MBSs) formed at the ends of a topological superconductor nanowire with spin-dependent coupling strength. By adjusting the sign of the spin polarization of dot-MBS coupling strength and the arrangement of magnetic moments of the two leads, the currents’ magnitude can be effectively enhanced or suppressed. Under some conditions, a negative TMR emerges which is useful in detection of the MBSs, a research subject currently under extensive investigations. Moreover, the amplitude of the TMR can be adjusted in a large regime by variation of several system parameters, such as direct hybridization strength between the MBSs or the dots, and the positions of the dots’ energy levels. Such tunable currents and TMR may also find use in high-efficiency spintronic devices or information processes.